Internet's Islamic information credibility scale (IIICS) - Ishak, Mohd Sobhi; Omar, Siti Zobidah; Bolong, Jusang; Abu Hassan, Musa; Abd. Ghani, Zulkiple (Penerbit Universiti Sains Islam Malaysia, 2011)
The present research develops and validates a new scale that measures Internet information credibility from Islamic perspective. The content domain for this measure was developed based on interviews with Islamic scholars, and previous literature on credibility, and empirically tested using a large samples of 1180 Internet users qualified in Islamic studies. Eight dimensions extracted from 85 developed items using exploratory factor analyses and namely: visual appeal, source-writer relationships, authentic source, writer’s moral, web reputation, writer’s integrity, writer’s identity, and writer’s reliance. The measurement model of multidimensional scale was validated using Structural Equation Modeling on AMOS Version 18. Thus, the re-specified model produced the Internet’s Islamic Information Credibility Scale with not only the content validity, but also displays the construct reliability, convergent validity, and discriminant validity.